Ecological review of the Syllidae (Annelida) associated with sponges (Porifera), including the description of a new species from northeastern Brazil - Anny Laura de Oliveira Lira; Nykon Craveiro; Karla Paresque; Marcelo Veronesi Fukuda; José Souto Rosa Filho (Ocean and Coastal Research)
This study reviews the data published on the ecology of polychaete annelids of the family Syllidae associated with sponges (Porifera) and provides additional empirical data from samples collected at Paiva Beach (northeastern Brazil). This literature review collected data from the Web of Science and Scopus databases, together with additional sources of information, to provide the best possible overview of the available data on the ecological relationships between these organisms. This review identified a total of 76 papers reporting on 68 associations between syllids and sponges, which involved 61 syllid species inhabiting 57 different sponge taxa. Although few studies have provided detailed data on the auto-ecology of the syllids associated with sponges, some information is available on their reproductive patterns, feeding habits, and role in the association. In this study, seven syllid genera were recorded inhabiting sponges of the genus Cinachyrella (Porifera: Tetillidae) at Paiva Beach in Pernambuco, northeastern Brazil, where a predominance of syllids of the genus Branchiosyllis was recorded. The syllids were found either on the outer surface of the sponges or in their inner channels, and most specimens were females, some of which presented stolons, indicating that they were using the sponges as a reproductive substrate. A new species of the genus Branchiosyllis is described based on our collected data. Branchiosyllis lanai sp. nov. can be identified by its relatively enlarged anterior region, cirriphore with a collar, and branchiae varying between domed and multilobed. The new species is compared with its morphologically most similar congeners. A synoptic table of the morphological variation found among the individuals of the type series is also provided, as well as an updated key to the identification of the Branchiosyllis species found on the Brazilian coast.